SOCIO-ECONOMIC MAPPING IN THE EMPOWERMENT OF INDIGENOUS COMMUNITIES THROUGH HUMAN RESOURCE MANAGEMENT - Sutrasna, Yudi (Universitas Padjadjaran, 2024)
This study aims to map the socio-economic conditions of the Indigenous Muyu Tribe as a basis for empowerment, reviewed from the perspective of Human Resource Management (HRM). The concept of empowerment used is based on the ideas of Amartya Sen (1999) and Robert Chambers, which emphasize the enhancement of capabilities as the key to empowerment. A community that is empowered socio-economically will have a strong resilience against threats. This study uses a case study design approach. Data were collected through in-depth interviews, observation, and document study. The data were analyzed using thematic analysis techniques. This study finds that the current socio-economic conditions of the Muyu Tribe are caused by various interrelated factors, which in this study are limited to the factors of limited access to education and livelihoods faced by the Muyu Tribe. Geographical factors and the tribe’s worldview or beliefs are discussed briefly. This study concludes that improving the capabilities of the Muyu Tribe can be an alternative form of empowerment that can be implemented to improve the socio-economic conditions of the Muyu Indigenous People from the HRM perspective, carried out through four (4) empowerment approaches: 1) human empowerment, 2) economic empowerment, 3) environmental empowerment, and 4) institutional empowerment. A socially and economically empowered Muyu Tribe will have high resilience in facing threats. Enhancing the capabilities of the Muyu Tribe through the four (4) empowerment approaches requires the role of external empowerment agents, namely: the central government, local government, education activists who understand local culture, and the private sector. This study contributes to the enrichment of HRM and defense economics studies, as well as the practice of empowerment and the formulation of community empowerment policies by making the cultural factors of local communities one of the determining variables.